Chronic Lymphocytic Leukemia B-Cell Normal Cellular Counterpart: Clues From a Functional Perspective - Darwiche, Walaa; Gubler, Brigitte; Marolleau, Jean-Pierre; Ghamlouch, Hussein (Frontiers in Immunology, 2018)
Chronic lymphocytic leukemia (CLL) is characterized by the clonal expansion of small mature-looking CD19+ CD23+ CD5+ B-cells that accumulate in the blood, bone marrow and lymphoid organs. To date, no consensus has been reached concerning the normal cellular counterpart of CLL B-cells and several B-cell types have been proposed. CLL B-cells have remarkable phenotypic and gene expression profile homogeneity. In recent years, the molecular and cellular biology of CLL has been enriched by seminal insights that are leading to a better understanding of the natural history of the disease. Immunophenotypic and molecular approaches (including immunoglobulin heavy-chain variable gene (IGHV) mutational status, transcriptional and epigenetic profiling) comparing the normal B-cell subset and CLL B-cells provide some new insights into the normal cellular counterpart. Functional characteristics (including activation requirements and propensity for plasma cell differentiation) of CLL B-cells have now been investigated for 50 years. B-cell subsets differ substantially in terms of their functional features. Analysis of shared functional characteristics may reveal similarities between normal B-cell subsets and CLL B-cells, allowing speculative assignment of a normal cellular counterpart for CLL B-cells. In this review, we summarize current data regarding peripheral B-cell differentiation and human B-cell subsets and suggest possibilities for a normal cellular counterpart based on the functional characteristics of CLL B-cells. However, a definitive normal cellular counterpart cannot be attributed on the basis of the available data. We discuss the functional characteristics required for a cell to be logically considered to be the normal counterpart of CLL B-cells.